Examining the Role of Principal Leadership Style and Educator Performance in Shaping Student Wellbeing - Ersari,; Hardiansyah,; Muhammad Iqbal, (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to examine the influence of principal leadership style and educator performance on students' wellbeing at SMPN 1 Bayan. This research employed a quantitative associative approach involving 100 students from grades 7 and 8 selected through proportional random sampling. Data were collected using questionnaires for three variables with 10 items each, which had been validated and tested for reliability. The data analysis technique used descriptive statistical analysis followed by multiple linear regression analysis. The results showed that simultaneously (F test), both variables are significant predictors of student wellbeing (F = 18.458, sig = 0.001). Partially (t test), principal leadership style significantly influences student wellbeing (b = 0.675, sig = 0.001), while educator performance does not show significant influence (b = 0.156, sig = 0.180). The coefficient of determination (R²) is 0.276, indicating that both variables explain 27.6% of the variance in student wellbeing. These findings suggest that principal leadership plays a more crucial role in creating student wellbeing compared to direct educator performance. Key Words: Principal Leadership Style, Educator Performance, Student Wellbeing. Abstrak: Penelitian ini bertujuan untuk mengkaji pengaruh gaya kepemimpinan kepala sekolah dan kinerja pendidik terhadap students wellbeing di SMPN 1 Bayan. Penelitian ini menggunakan pendekatan kuantitatif asosiatif yang melibatkan 100 siswa kelas 7 dan 8 yang dipilih melalui proportional random sampling. Data dikumpulkan menggunakan angket untuk tiga variabel dengan masing-masing 10 butir yang telah divalidasi dan diuji reliabilitasnya. Teknik analisis data menggunakan analisis statistik deskriptif dilanjutkan dengan analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa secara simultan (uji F), kedua variabel merupakan prediktor signifikan terhadap student wellbeing (F = 18,458, sig = 0,001). Secara parsial (uji t), gaya kepemimpinan kepala sekolah berpengaruh signifikan terhadap student wellbeing (b = 0,675, sig = 0,001), sedangkan kinerja pendidik tidak menunjukkan pengaruh signifikan (b = 0,156, sig = 0,180). Koefisien determinasi (R²) sebesar 0,276 menunjukkan bahwa kedua variabel menjelaskan 27,6% varians dalam student wellbeing. Temuan ini mengindikasikan bahwa kepemimpinan kepala sekolah memiliki peran yang lebih krusial dalam menciptakan kesejahteraan siswa dibandingkan kinerja pendidik secara langsung. Kata Kunci: Gaya Kepemimpinan Kepala Sekolah, Kinerja Pendidik, Kesejahteraan Siswa.